Reconciliation : Islam, Democracy, and the West - Benazir Bhutto (London Simon & Schuster, 2008)
English Biography.
Include Notes.
Islam, Democracy, and the West.
Keywords: Islamic countries -- Islam and politics -- Pakistan -- Islam